Implementation Plan in Response to the Board-Endorsed Recommendations for the IEO Evaluation Report of IMF Response to the Financial and Economic Crisis. (Policy Papers; Policy Paper ;, 2015)
This paper sets out Management's response to the Independent Evaluation Office's (IEO) evaluation of IMF Response to the Financial and Economic Crisis. The implementation plan proposes specific actions focusing on the three of the four recommendations that received broad support from the Executive Board, namely (i) ensuring that the IMF as a quota-based institution has sufficient resources to contribute to future crisis resolution; (ii) developing guidelines for structuring engagements with other organizations, and (iii) consolidating and simplifying the current framework to identify and assess risks and vulnerabilities. Some of the proposed actions to address the Board-endorsed IEO recommendations are underway as part of the 2014 Triennial Surveillance Report (TSR) Action Plan, the FY2016-18 Medium-Term Budget and the ongoing efforts to ratify the 2010 Quota and Governance Reforms. The paper also explains how implementation will be monitored.